Implementation of Behavioristic Theory as an Effort to Increase Writing Delay in terms of Internal and External Factors of Students - I Komang Ngurah Jaya Laksana; Ni Ketut Suarni; I Gede Margunayasa (Psikostudia : Jurnal Psikologi, 2023)
Research focused on writing delays in 40 elementary school students showed a pattern that confirmed serious difficulties in writing skills. The data highlights that 25% of students experience low lateness, 45% with moderate late rates, and 30% face high lateness. This underscores the importance of educational interventions that are focused on and tailored to individual needs. This research highlights the importance of deep understanding of students' root causes, curriculum improvement, training for educators, and strengthening writing skills as the focus in the learning approach. Identification of factors that cause writing delays, such as learning environment, individual differences, and health aspects, is an important foundation in designing adaptive learning approaches. This finding emphasizes the need for integration of teaching methods that suit the needs and use of technology to increase student interest. This research makes a significant contribution to efforts to develop more effective educational strategies, especially in overcoming the challenges of late writing and reading among elementary school students.Penelitian yang difokuskan pada keterlambatan menulis pada 40 siswa SD Mahardika Denpasar menunjukkan pola yang menegaskan kesulitan yang serius dalam kemampuan menulis. Data menyoroti bahwa 25% siswa mengalami keterlambatan rendah, 45% dengan tingkat keterlambatan sedang, dan 30% menghadapi keterlambatan tinggi. Hal ini menggarisbawahi pentingnya intervensi pendidikan yang terfokus dan disesuaikan dengan kebutuhan individu. Penelitian ini menyoroti pentingnya pemahaman yang dalam terhadap akar permasalahan siswa, peningkatan kurikulum, pelatihan bagi para pendidik, serta penguatan keterampilan menulis sebagai fokus utama dalam pendekatan pembelajaran. Identifikasi faktor-faktor penyebab keterlambatan menulis, seperti lingkungan belajar, perbedaan individual, dan aspek kesehatan, menjadi landasan penting dalam merancang pendekatan pembelajaran yang adaptif. Temuan ini mempertegas perlunya integrasi metode pengajaran yang sesuai dengan kebutuhan serta penggunaan teknologi untuk meningkatkan minat siswa. Penelitian ini memberikan sumbangan yang signifikan dalam upaya pengembangan strategi pendidikan yang lebih efektif, khususnya dalam mengatasi tantangan keterlambatan menulis dan membaca di kalangan siswa sekolah dasar.